Sensitivity of SARS-CoV-2 Detection With Nasopharyngeal Swabs - Clerici, Bianca; Muscatello, Antonio; Bai, Francesca; Pavanello, Donatella; Orlandi, Michela; Marchetti, Giulia C.; Castelli, Valeria; Casazza, Giovanni; Costantino, Giorgio; Podda, Gian Marco (Frontiers in Public Health, 2021)
Background SARS-CoV-2-infected subjects have been proven contagious in the symptomatic, pre-symptomatic and asymptomatic phase. The identification of these patients is crucial in order to prevent virus circulation. No reliable data on the sensitivity of nasopharyngeal swabs (NPS) are available because of the lack of a shared reference standard to identify SARS-CoV-2 infected patients. The aim of our study was to collect data on patients with a known diagnosis of COVID-19 who underwent serial testing to assess NPS sensitivity. Methods The study was a multi-center, observational, retrospective clinical study with consecutive enrollment. We enrolled patients who met all of the following inclusion criteria: clinical recovery, documented SARS-CoV-2 infection (≥1 positive rRT-PCR result) and ≥1 positive NPS among the first two follow-up swabs. A positive NPS not preceded by a negative nasopharyngeal swab collected 24-48 hours earlier was considered a true positive. A negative NPS followed by a positive NPS collected 24-48 hours later was regarded as a false negative. The primary outcome was to define sensitivity of SARS-CoV-2 detection with NPS. Results 393 NPS were evaluated in 233 patients; the sensitivity was 77% (95% CI, 73 to 81%). Sensitivity of the first follow-up NPS (n=233) was 79% (95% CI, 73 to 84%) with no significant variations over time. We found no statistically significant differences in the sensitivity of the first follow-up NPS according to time since symptom onset, age, sex, number of comorbidities and onset symptoms. Conclusions NPS utility in the diagnostic algorithm of COVID-19 should be reconsidered.